XIX & XX Century : Paintings, Works on Paper and Sculptures - Galerie Patrick Derom, Brussels (Brussel : Galerie Patrick Derom Brussel, 1990)
Alechinsky, Pierre ; Baugniet, Louis-Marcel ; Delescluze, Edmond ; De Smet, Gustave ; De Smet, Léon ; Jefferys, Marcel ; Jespers, Floris ; Khnopff, Fernand ; Lacasse, Joseph ; etc.
XIX & XX Century : Paintings, Works on Paper and Sculptures, Galerie Patrick Derom, Brussel, Autumn 1990
boek